Preexisting conditions recounting the plague - Weber, Samuel, 1940- (Zone Books, 2022)
"Plagues and pandemics confront societies with something they often seek to deny, namely that mortality and vulnerability is not just an individual concern. The narratives examined in this book both confirm the desire to avoid this recognition as well as the different ways it asserts itself nevertheless"--